PENGARUH NON-PERFORMING LOAN, RETURN ON ASSETS, CAPITAL ADEQUACY RATIO, DAN OPERATING COST AND OPERATING INCOME TERHADAP FINANCIAL SUSTAINABILITY - Sudrajat, Kansa Dwi Putri Angelina; Ariani, Yovita (LPPM Universitas Bina Bangsa, 2025)
This study aims to obtain empirical evidence related to the effect of non-performing loans, return on assets, capital adequacy ratio, and operating cost and operating income (BOPO) on financial sustainability. The population in this study are banking sub-sector companies listed on the Indonesia Stock Exchange. The research method used is quantitative research method. The sample in this study was collected using nonprobability sampling method with purposive sampling technique. The results of this study indicate that the variable return on assets, capital adequacy ratio, and operating cost and operating income have an influence on financial sustainability. While the non-performing loan variable has no influence on the financial sustainability ratio